Specific traits of neo-Weberian states on the example of their reaction to the global financial crisis - Białynicki-Birula, Paweł; Klich, Jacek (Journal of Public Governance, 2018)
The goal of the paper is to inquire to what extent neo-Weberian states (NWS) identified by Pollitt & Bouckaert (2011) differentiated their policies in reaction to the global financial crisis of 2007/2008. The paper is based on desktop studies from ScienceDirect and OECD. In the first part of the paper, the sources of the concepts of neo-Weberian states are presented, followed by characteristic traits of public policies. The core of the paper is a presentation of the policies of neo-Weberian states on the one hand, and of New Public Management states on the other, in their reaction to the global financial crisis. The paper concludes that the eleven analyzed countries reacted to the global financial crisis in different ways and to a different degree. Their reactions ref lected their national models of financial capitalism (Grittersová 2014) rather than the categories identified by Pollitt & Bouckaert (2011)